2020
DOI: 10.3390/ma13051061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Filling Rate on Underwater Wet Welding Process and Weld Appearance

Abstract: Real-time electric signal, matter transfer mode and welding pool behavior were obtained to investigate the effect of wires’ filling rate on arc stability and joints’ appearance during underwater wet flux-cored arc welding (FCAW). The electric signal results showed that arc stability first decreased and then increased rapidly because the raise of filling rate affected the number of charged particles and the electrical conductivity of welding arc atmosphere. Two typical transfer modes, globular repelled transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Zhang et al [10] proved that unstable welding arc generates problem with droplet transition, which may cause geometric shape imperfections. Zhang et al [11] in their next research performed experiments, which showed the possibility of increasing the stability of the welding arc by selecting the appropriate parameters. Yang et al [12] compared the shape of welding arc under water and in air environment using similar welding parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [10] proved that unstable welding arc generates problem with droplet transition, which may cause geometric shape imperfections. Zhang et al [11] in their next research performed experiments, which showed the possibility of increasing the stability of the welding arc by selecting the appropriate parameters. Yang et al [12] compared the shape of welding arc under water and in air environment using similar welding parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The flow rate of shielding gas is about 20 L/min. The preheating and inter-pass temperature was 150 groove pressing formation, flux filling, rolling sealing and diameter reduction, as shown in Figure 1 [28]. The base metal used in this experiment was Q345 steel, which is used as the substrate with no effect on sampling, playing a supporting role to prevent molten pool flow and improve molding.…”
Section: Methodsmentioning
confidence: 99%
“…They are made of a metal sheath filled with ceramic or metallic powder. With such a structure, it is possible to achieve a favorable spray metal transfer in the welding arc, higher wire melting rates and the use of the core of wire for metallurgical purposes [ 18 , 19 ]. The consumption of flux-cored wires for ocean and marine structures is still increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great practical significance of problems associated with the storage of welding consumables, this topic is relatively rarely discussed in the literature. Previous works mainly concerned the impact of wire construction and storage conditions on the diffusible hydrogen amount in weld metal [ 18 , 22 , 38 ] and the influence of welding parameters and conditions on the quality and properties of welded joints [ 20 , 39 , 40 , 41 , 42 ]. Accordingly, the purpose of the work was to analyze the impact of storage conditions of seamless, copper plated flux-cored wires on the plasticity of the bead-on-plate welds made with these wires.…”
Section: Introductionmentioning
confidence: 99%